Oridonin Alleviates LPS-Induced Depression by Inhibiting NLRP3 Inflammasome via Activation of Autophagy - Li, Chunyan; Zhu, Yuehua; Wu, Yuanyuan; Fu, Meiyuan; Wu, Yiling; Wu, Yuehong; Qiu, Yinger; Zhang, Hui; Ding, Mingxing (Frontiers in Medicine, 2022)
Objective: Oridonin (Ori) is a diterpene compound that has multiple biological properties. Here, our study was conducted to observe the therapeutic effect of Ori on depression as well as to uncover the mechanism. Methods: Lipopolysaccharide (LPS)-induced depression models were established both in C57BL/6 mice and primary astrocytes, which were treated with Ori, autophagy agonist Rapamycin (Rap) and autophagy inhibitor 3-Methyladenine (3-MA). The depressive-like behaviors were assessed with behavioral tests. Autophagy was evaluated in the hippocampus and astrocytes by investigating autophagosomes under transmission electron microscope (TEM) and detecting LC3II/I, Beclin1 and P62 through western blotting. Astrocyte marker glial fibrillary acidic protein (GFAP) was investigated by immunofluorescence. NLRP3 inflammasome activation was evaluated by detecting IL-1β, NLRP3, ASC and Caspase-1 expression and reactive oxygen species (ROS) accumulation was quantified via DCFH-DA probe. Autolysosomes, autophagosomes and mitophagy were separately observed through mTag-Wasabi-LC3 plasmid, MitoTracker Deep Red staining, and TEM. Results: Our results showed that Ori administration alleviated LPS-induced depressive-like behaviors and increased GFAP expression in the hippocampus. Furthermore, Ori treatment promoted autophagy activation and cell viability as well as weakened NLRP3 inflammasome activation and ROS accumulation both in LPS-induced mice and astrocytes. Ori promoted the autophagic flux unblocked through enhancing fusion of autophagosomes with lysosomes as well as enhanced mitophagy in LPS-treated astrocytes. The therapeutic effect of Ori was enhanced by Rap and weakened by 3-MA. Conclusion: Collectively, our findings provided a promising antidepressant drug and uncovered that Ori alleviated LPS-induced depression by inhibiting NLRP3 inflammasome through activation of autophagy.